2001
DOI: 10.1002/1097-0215(200002)9999:9999<::aid-ijc1103>3.3.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Tissue‐specific alternate splicing of human telomerase reverse transcriptase (hTERT) influences telomere lengths during human development

Abstract: Direct genetic manipulations have shown that telomerasemediated telomere elongation plays a key role in determining cellular replicative capacity and senescence. The mechanisms regulating the production of an active telomerase enzyme are still predominantly unknown, although roles for transcriptional control of hTERT, alternative-splicing of hTERT transcripts, and post-translational phosphorylation of hTERT protein have been advocated. Here we show that hTERT is alternatively spliced in specific patterns by di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
3

Year Published

2002
2002
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 1 publication
2
53
0
3
Order By: Relevance
“…Alternative splicing machinery of hTERT is considered to be tissue specific and to influence telomere lengths during human development (Ulaner et al, 2001). It has been shown that hTERT RNA alternative splicing mediates telomerase downregulation induced by the G-quadruplex ligand 12459 (Gomez et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Alternative splicing machinery of hTERT is considered to be tissue specific and to influence telomere lengths during human development (Ulaner et al, 2001). It has been shown that hTERT RNA alternative splicing mediates telomerase downregulation induced by the G-quadruplex ligand 12459 (Gomez et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These assays examine the aggregate of numerous cell types present in whole tissue samples, including migrating or circulating cells present at the time of the assay (for example, fetal spleen and liver are sites of hematopoiesis). However, some correlation can be made between telomerase inactivation, di erentiation and increased rate of telomere loss with time (Ulaner and Giudice, 1997;Ulaner et al, 2001). In heart tissue, loss of activity occurs concomitant with loss of TERT mRNA expression; loss of activity in kidney instead occurs concomitant with a change in the pattern of TERT pre-mRNA splicing (Ulaner et al, 1998).…”
Section: Tissue Specificity and Developmental Regulationmentioning
confidence: 99%
“…5 Several splice variants of the hTERT gene transcript have been described. 9,10 However, it is generally accepted that only the full-length transcript of the hTERT gene can function as the catalytic subunit of telomerase, since it contains the whole core catalytic domain and the specialised carboxy-terminus of this transcriptase. 11 We have recently demonstrated that telomerase catalytic subunit (hTERT) mRNA relative quantities increase progressively with the degree of laryngeal epithelial abnormalities by using RT-PCR, and hypothesised that hTERT gene re-expression represents an early event in the multistep process of laryngeal carcinogenesis.…”
mentioning
confidence: 99%